Hubungan Tingkat Asupan Energi dan Protein Dengan Kejadian Gizi Kurang Anak Usia 2-5 Tahun - Hapsari Sulistya K; - Sunarto (Jurnal Gizi, 2013)
The prevalence of undernutrition on the children under 5 years old in Pulutan village is 6,9% it is higher than the others. Undernutrition is caused by some factors; food intake, infection, pattern of care, food pattern, cultural habit, healthy care, sanitation, education, knowledge, economic, politic, and social. The purpose of this research is to find the relation between energy intake and protein intake factors of undernutrition children age 2-5 years. The method used in this research is case control design. Population are children age 2-5 years who get undernutrition and wellnutrition in Pulutan village. Sampel are 21 cases and 21 controls by random. Independent variables are energy intake and protein intake.Dependent variable is children nutritional status. The data nutritional status were gathered using standart antropometric prosedures, the data of energy and protein intake were gathered from recall 2x24 hours. Corellation between variables were tested using Chi Square or FisherExact and multiple regressions logistic. There is relation between protein intake with nutritional status (x2=4,725; p=0,03). There is not relation between energy intake with nutritional status (x2=1,003; p=0,317). Byusing multiple regression logistic there is relation between protein intake with nutritional status (p=0,042; RP=14,4), relation energy intake with nutritional status (p=0,802; RP=0,7). The Conclusion is Determinant factor undernutrition children age 2-5 years of Pulutan village is protein intake.Keywords : energy intake, protein intake, undernutrition, children age 2-5 years.